2020
DOI: 10.31024/apj.2020.5.1.4
|View full text |Cite
|
Sign up to set email alerts
|

An in ovo investigation on antiviral activity of Cannabis sativa extracts against Newcastle Disease Virus (NDV)

Abstract: A central tenet underlying the use of plant preparations is that plants contain many bioactive phytochemical compounds used for myriad of pharmacological purposes (Maria, 2016). One of the earliest used plants in history is as fossil Cannabis sativa record data reveals the regular use of plant extracts by humans for therapeutic purposes (Alfred, 2013; Federica et al., 2018). From that point, the development of traditional medical system incorporating plants as a means of therapy can be traced back only as far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These compounds corresponded with those reported by Aslam et al (2009). Similarly, Abubakar et al . (2020) in their studies on the phytochemical constituents of petroleum ether, ethyl-acetate and methanolic extracts of .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These compounds corresponded with those reported by Aslam et al (2009). Similarly, Abubakar et al . (2020) in their studies on the phytochemical constituents of petroleum ether, ethyl-acetate and methanolic extracts of .…”
Section: Discussionmentioning
confidence: 74%
“…Some of the plants have been found to possess significant antibacterial, antifungal, anticancer, antidiuretic, anti-inflammatory and antidiabetic properties (Sule et al, 2010;Timothy et al, 2012;Adelowo and Oladeji, 2016). Whole plants, leaves and wood have environmental uses, bark, fiber and seeds are also of ritual importance (Esra et al, 2012;Abubakar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Findings of our previous study on the phytochemical constituents of plant extracts revealed that C. sativa C. sativa leaves and seeds extracts are rich source of alkaloid, flavonoid, tannins, phenol, steroids, glycoside, saponins and triterpenoid (Abubakar et al, 2020b). The presences of these secondary metabolites that are biologically active are responsible for the antibacterial activities of .…”
Section: Discussionmentioning
confidence: 99%
“…The result of the phytochemical analysis of plant C. sativa extracts using petroleum ether and methanol solvents is presented in our earlier study (Abubakar et al, 2020b).…”
Section: Phytochemical Analysis Of Plant Extracts C Sativamentioning
confidence: 99%
“…THC (10 µM) exhibited a reduction of simian immunodeficiency virus (SIV) replication in MT4-R5 cells, which was administered 28 days prior to virus inoculation [ 138 ]. C. sativa plant extracts exhibited significant antiviral activity ( p < 0.05) against Newcastle disease virus (NDV) [ 139 ]. THC inhibited lytic replication and reactivation of gamma herpesvirus, which indicates that ECS is possibly involved in regulating its latency.…”
Section: Antiviral Activity: Special Focus On Sars-cov-2mentioning
confidence: 99%